Problematics of Contemporary Problems and Cultural Poverty Challenges - Hakis, Hakis; Rahman, Rahman; Syahputra , Dedek; Yakir , Julia (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
The more serious problems of contemporary da'wah today align with the continued development of increasingly complex social human life, one of which is the challenge of cultural poverty. Implementing the da'wah function at least motivates the da'wah target always to try to avoid poverty. The purpose of this research is to find solutions to the problems of contemporary da'wah in terms of facing the challenges of cultural poverty experienced by people who are passive in trying, including those who face fatalistic thoughts about sustenance that has been arranged by Allah SWT so that there is no need to try to find food. The research method used is qualitative research with a library research approach. The study results show that contemporary da'wah's problems have faced various challenges and difficulties, both internally and externally. The challenge of cultural poverty finds at least four classifications of discussion: forms of cultural deprivation, the impact of cultural lack, the causes of poverty, poverty, and its alleviation strategies. Furthermore, the function of da'wah in overcoming cultural poverty will only be optimally achieved if the community realizes the importance of effort and hard work, including increasing the application of social care among fellow believers, which is very much needed in social life.